Market in American Education as a Theory and Ideology - Potulicka, Eugenia (INSTED: Interdisciplinary Studies in Education & Society, 2012)
If the research results serve their purposes, the supporters of specific ideologies make use of them in political actions such as educational reforms. That does not leave too much room for neutrality. The fact is that the debates on education have always been political struggles about who shall specify what should be taught. The two decades of attempts to integrate the public education system with the market brought about sectarian controversies in the USA. The supporters of a democratic school are convinced that its major aim is to shape citizenship as a way of living, while the advocates of a market school think that such aim consists in shaping consumption as a way of living. The latter ones say that they put forward instrumental means to achieve the required and universal targets. The conflict between these camps is normative and philosophical. It focuses on the question who and what shall set up political aims of public education. The key question in this dispute is a question whether the market is a utilitarian and instrumental answer to a clearly specified set of educational problems or whether it is an ideological agenda. The clarification of positive and normative dimensions of market theory and neoliberal ideology will be one of the aims of this paper.